Digitalisasi Sastra Kontemporer Lewat Grafik Novel “Tabi” Karya Marchella FP - Liana, Patricia; Riyanto, Edi Dwi; Afdholy, Nadya (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
The digitization of literature is one of the effects of the postmodern era that cannot be avoided. This literaturebased qualitative research investigates the development of postmodernism in literature, with a primary emphasis on its principles and implications in modern literature. This research aims to find out how postmodernism, especially in the digital era, has an impact on the recognition and sales of modern literary works. Using Marchella FP's novel "Tabi", which was released as a case study in October 2023, this study investigates the role of social media platforms, especially TikTok, in promoting and selling literature. This research emphasizes the important implications of digital postmodernism for future prospects by emphasizing paradigm shifts and enhanced inclusivity in the digital world. Additionally, this research examines the idea of viral marketing and how it relates to spreading literary works through social media platforms such as TikTok. Keywords: Contemporary Literature, Literary Digitization, Postmodernism.